International Financing Decision: A Managerial Perspective - Cristian PĂUN (Revista de Management Comparat International)
International financial decision is not a simple one and it is mainly characteristic to multinational companies or to companies located in countries with a reduced saving rate that is not sufficient to cover all internal financing needs (is the case of emerging markets like Romania is). The financial managers of Romanian companies need to have tools to decide if they will use a credit in lei from local banks or will try to obtain a credit from abroad in a foreign currency (in Euro, USD etc.). The required assumption in this case is that capital account between Romania and other countries is totally free. This decision is not a simple one and it should be based on theoretical background. The financing decision depends upon two main criteria: cost and risks assumed by the company. This paper will discuss the solution in this case to compare different international financing opportunities that are expressed in different currencies from the perspective of a debtor (company).